(untitled) (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2012)
Objective: To determine the relationship between the prevalence of back pain, insufficient knowledge of postural hygiene, and physical activity in a group of university students. Methodology: A survey on lifestyle habits was administered to a sample of 548 university students (431 women and 117 men, mean age: 20 years SD: 2.317) to obtain information related to back pain, the Postural Hygiene Knowledge Questionnaire to assess back management, and the abbreviated version of the International Physical Activity Questionnaire, which measures the intensity, duration, and frequency of activity in the last week. The prevalence of back pain, the score for proper spine management, and physical activity levels were calculated. Finally, Cramer’s V test was applied to establish associations between variables. Results A prevalence of back pain of 78% was found, which was reported by more women than men, with these differences being significant. The area most frequently affected by pain is the cervical region. The main cause of back pain was attributed to poor posture. Sixty-three percent of students had sufficient knowledge about proper spine management. Regarding physical activity, 80% of university students were found to be regularly active, and of this percentage, 52% had a high level of physical activity. No statistically significant relationships were found between physical activity and back pain (x2 = 0.587; p = 0.964). However, as the level of activity increases, so does the level of knowledge about postural hygiene. This relationship was statistically significant (x2 = 6.456; 0.040). Conclusions Although satisfactory levels of knowledge about postural hygiene for neck and back care were detected, a high percentage of students reported having suffered from back pain. Although high levels of physical activity were found, some university students still do not meet the minimum recommended parameter for health benefits. Physical activity is associated with knowledge of postural hygiene but not with back pain. The university should provide opportunities for physical activity and appropriate habits for back care.